2015
DOI: 10.2196/jmir.4420
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Frequency of mHealth and eHealth Use Among US and UK Smokers and Differences by Motivation to Quit

Abstract: BackgroundBoth mHealth and eHealth interventions for smoking cessation are rapidly being developed and tested. There are no data on use of mHealth and eHealth technologies by smokers in general or by smokers who are not motivated to quit smoking.ObjectiveThe aims of our study were to (1) assess technology use (eg, texting, social media, Internet) among smokers in the United States and United Kingdom, (2) examine whether technology use differs between smokers who are motivated to quit and smokers who are not mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 32 publications
1
50
0
1
Order By: Relevance
“…Studies have shown inconsistent correlation on app utilization and acceptance. Online and mHealth studies face challenges regarding ideal participant yield and fluctuating costs of online recruitment 19,48 . The theory based app features are employed in our studies with limited information on the quality of this evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown inconsistent correlation on app utilization and acceptance. Online and mHealth studies face challenges regarding ideal participant yield and fluctuating costs of online recruitment 19,48 . The theory based app features are employed in our studies with limited information on the quality of this evidence.…”
Section: Discussionmentioning
confidence: 99%
“…One comparative study suggested a large number of smokers use the smartphone to send and receive texts, download apps, use Facebook, and browse health-related internet sites 19 . Evaluation of evidence of the impact and cost-effectiveness of mHealth services is imperative, as the modifiable gap in communication persists between healthcare professionals and smokers 20 .…”
Section: Introductionmentioning
confidence: 99%
“…A call within the first week of a quit attempt post-discharge would be ideal, as many smokers relapse within the first week of discharge. 51 Until smokers feel able to participate in real-time counseling, asynchronous methods for interacting with smokers, such as text messaging or other mobile or Internet methods, 52 might help them stay committed to quitting during their post-hospital recuperation. Text messaging has the added advantage of being a low-cost, effective method for smoking cessation that is globally affordable.…”
Section: Discussionmentioning
confidence: 99%
“…Of late, scholars have been focusing on the use of technology in smoking cessation interventions. 4143 Although this may have merit, scholars have found the use of technology to be dependent on one’s motivation to quit, 41 to vary by participant characteristic (eg, women, low education, heavy smokers were less likely to use cessation apps), 43 and by population group. 42 Future research may benefit by testing how mobile apps could be used in conjunction with face-to-face mode of content delivery.…”
Section: Discussionmentioning
confidence: 99%